QUERIÓN DE CELSO: UNA COMPLICACION RARA DE LA TIÑA CAPITIS - , A, Cvetkovic-Vega (2018)
Abstract Kerion Celsi is a rare complication of Tinea Capitis caused by an hyperreaction to a Type 4 Hypersensibility against the fungus. We are presenting a case from a peruvian 9 year old boy with a 20 days illness in which it is described a painful, pruriginous alopecia plate covered by myeleric crust and suppuratives abscesses with boggy mass at the right parietal region. The clinical diagnosys was made, and later confirmed by the agent cultive in which was trichopyton tonsurans. A treatment with Terbinafine for 4 weeks, prednisone 7 days and clindamicine for 10 days was started, with a favorable evolution. Key words: Kerion Celsi; Complication; Tinea capitis; Trichophyton tonsurans. (source: MeSH NLM) DOI: https://doi.org/10.25176/RFMH.v18.n1.1272